Investigation into technological parameters of bitumen batching in an asphalt mixing plant - Bražiūnas, Justas (Journal of Civil Engineering and Management, 2015)
An appropriate bitumen content and its properties in hot mix asphalt (HMA) mixture impact on the long-term mechanical strength of the laid asphalt pavement and the required road operation properties. During the production of a HMA mixture in an asphalt mixing plant (AMP), relationships between the structure and interaction of the mixture are established based on technological processes that specify bitumen batching and component mixing. These processes ensure the long-term strength, texture, evenness, the degree of damage and rheological properties of road pavement. The presented mathematical model enables us to determine the distribution of oxygen pressure by time in differently sized drops of bitumen during their fall into a mixer. The model considers oxygen diffusion, which depends on temperature, and heat conductivity, which depends on temperature, density and specific heat. An active experimental investigation under real production conditions demonstrated that the method of bitumen discharge from a batcher, temperature and time spent mixing materials with hot mineral aggregates impact on properties of bitumen binder within the produced HMA mixture. Parameters of technological processes for mixing of bitumen with mineral aggregates that occur in a bitumen batching system (BBS) are stochastic and impact on the composition of bitumen binder as well as physical and mechanical properties of the produced HMA mixture, namely, air void content, stability, flow and Marshall quotient.